Sustainability status of Indian states: Application and assessment of MCDM frameworks - Sen, Nandita; Ghosh, Akash; Saha, Arnab; Karmaker, Bhaskar Roy (2014 IEEE Symposium on Computational Intelligence in Multi-Criteria Decision-Making (MCDM), 2014)
The evidence of UNDESA framework of sustainability assessment in MCDM paradigm is scarce generically and particularly, the status of sustainability of Indian states has never been assessed in accordance with UNDESA 2007 framework. This paper is an attempt to explore the paradigm of Multi-criteria Decision Making (MCDM) Methods in construction of sustainability index. To do so, we have used methods namely, Simple Additive Weighted Sum (SAWM), ELECTRE II, TOPSIS, PROMETHEE on the United Nations CSD indicators framework to evaluate the sustainability status of different states of India, which is among the fastest growing countries of todays world. We also try to understand the relative stability and distributional property of sustainability ranks obtained by different states. The ranks obtained by the different Methods are found to be relatively stable in comparative aspect. This implies that the choice of method does not make a big difference if the policy makers are interested for a group of entities to reward the superiors and support the laggards. On the other hand, a comprehensible and tractable method can be recommended for policy practice instead of less comprehensible one. Of course, use of a compendium of MCDM methods is always preferable for robustness analysis in decision-analytic aspect.